Exploring the implications of ternary Jeffrey nanofluid on pulsating flow and heat transfer through unsymmetrical corrugated micro conduit - Mohamed S. Abdel-wahed; Khaled S. Mekheimer; Ahmed Y. Sayed; Shaaban I. Ahmed (Results in Physics)
Pulsatile flow occurs in medical devices, impacting heat transfer and fluid behavior. It has practical significance in several disciplines, including thermodynamic devices. Pulses in flow and pressure influence pipe systems, reciprocating pumps, and compressors. Motivated by this, we simulated corrugated microchannel with Jeffery fluid flow enhanced by tri-nanoparticles to investigate this type of flow in detail. The model assumed that, in addition to external temperature influences, conduit walls experience electric and magnetic fields, governed by momentum and heat equations, along with electric potential and pulsing pressure equations. Using the perturbation method and Mathematica software, we derived semi-analytical solutions for the governing partial differential equations in their complex form. nanoparticle-enhanced blood exhibits improved thermal performance compared to pure fluid, with the type and concentration of nanoparticles (Fe3O4, Au, SWCNTs) significantly impacting heat dissipation and temperature distribution within the microfluidic conduit. Higher nanoparticle concentrations increase liquid viscosity, reducing velocity inside the conduit; however, a magnetic field can reverse this effect. This study underscores the application of pulsatile flow in heart pumps, where optimizing thermal characteristics can enhance device efficiency and patient outcomes.